Instant Self-Assembly of Functionalized MXenes in Organic Solvents: General Fabrication to High-Performance Chemical Gas Sensors - Kim, Soobin; Ko, Tae Yun; Jena, Ajit K.; Nissimagoudar, Arun S.; Lee, Juyun; Lee, Seongeun; Oh, Taegon; Kang, Yun Chan; In, Insik; Bhattacharjee, Satadeep; Koo, Chong Min; Lee, Seung-Cheol; et al. (John Wiley & Sons Ltd., 2024)
MXenes are a promising class of two-dimensional transition metal carbides, nitrides, and carbonitrides, widely utilized in diverse fields such as energy storage, electromagnetic shielding, electrocatalysis, and sensing applications. Their potential in chemical sensing is particularly noteworthy, where optimizing surface chemistry for strong interaction with target analytes and increasing surface area for efficient gas adsorption are crucial factors. In this study, a versatile and general self-assembly method for fabricating nanometer-scale thin films of surface-functionalized MXene, enabling high-performance gas sensors is developed. By dropping MXene dispersed in organic solvents onto nonsolvents, rapid formation of nanometer-scale films is achieved. This method allows easy adjustment of film properties by using different solvent-nonsolvent combinations, leading to improved optoelectronic properties compared to conventional techniques. The surface-functionalized MXenes using ADOPA ligands greatly enhance the gas response and long-term environmental stability compared to pristine MXenes. Computational methods are also employed to gain insights into the molecular interactions and changes in electronic structure that contribute to the enhanced sensing properties. Furthermore, the environmental stability of MXene sensors is largely enhanced after surface functionalization, which can be attributed to increased surface hydrophobicity. Overall, this innovative technique opens up opportunities for tailoring MXene thin films for specific applications. A versatile and general self-assembly method for fabricating nanometer-scale thin films of surface-functionalized MXene is demonstrated. By dropping MXene dispersed in organic solvents onto nonsolvents, instant formation of MXene films is achieved within 10 s where this method leads to MXene films with improved optoelectronic properties and gas-sensing properties.image